PONOROGO, THE LITTLE JAVA: POTRET KEBUDAYAAN DAN KEBERAGAMAAN MASYARAKAT MUSLIM PONOROGO ABAD XX - Arik Dwijayanto; Dawam Multazamy Rohmatulloh (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
In their daily life, Moslem society in Ponorogo holds tightly their ancestors' local tradition and culture. This situation is a condition that existed since the coming and developing era of this religion in Ponorogo and still exists until nowadays. The existence of Islam in Ponorogo that still exists should be recognized as one of the results of caring it together with the tradition or culture. The patterns of religiosity by keeping the local tradition as long as it isn't in contrary with Islam value, through a continuously transformation, finally strengthen the teaching of Islam in Ponorogo.This research aims the comprehensive portrait of the effect of religion and culture relationship in daily life of Moslem society in Ponorogo, especially in 20th.This research is a qualitative research by socio-history approach. By using history research methodology which is a method to examinate and critically analize the records and trails of the past, the author performs data mining from the written document, especially of the Babads and the Nederlands-Indie colonial archieve, interviews, and also the observations.This research concludes that the existential journey of Islam in Ponorogo was developed in two ways. Firstly, a legally and formally Islamization under the reign of the first regent of Ponorogo, Adipati Bathara Katong. Secondly, a cultural Islamization by preacher-santri's who came to Ponorogo from Demak as followers of Bathara Katong.These two ways create two different characteristics of Islam in Ponorogo. When Islam be preached by the first approach, a rejection by local people arised so that Islam character became hard. While otherwise, by the second cultural approach, a peaceful Islam thrived and finally Islam could be widely spread in Ponorogo.The encounter of Islam and local culture of Ponorogo finally creates a new synthesis: Ponoragan Moslem.